Suzuki–Miyaura cross coupling is not an informative reaction to demonstrate the performance of new solvents - James Sherwood (Beilstein Journal of Organic Chemistry, 2020)
The development and study of new solvents has become important due to a proliferation of regulations preventing or limiting the use of many conventional solvents. In this work, the suitability of the Suzuki–Miyaura reaction to demonstrate the usefulness of new solvents was evaluated, including Cyrene™, dimethyl isosorbide, ethyl lactate, 2-methyltetrahydrofuran (2-MeTHF), propylene carbonate, and γ-valerolactone (GVL). It was found that the cross coupling is often unaffected by the choice of solvent, and therefore the Suzuki–Miyaura reaction provides limited information regarding the usefulness of any particular solvent for organic synthesis.